PENGARUH CAPITAL ADEQUACY RATIO (CAR), PERFORMING LOAN (NPL), ANTAR BANK PASIVA (ABP), DAN DANA PIHAK KETIGA (DPK) TERHADAP PENYALURAN KREDIT PD BPR JAWA TENGAH - Vhaffrixca Aiffani, 10.05.52.0096; Masdjojo, Gregorius N. (Students Journal of Accounting and Banking, 2014)
Bank is the financial institution possessing function as the financial intermediary. Bank accepts the money savings from the society and then redistributes them upon the credit. The credit distribution creates opportunity to complete investment, distribution, and also the consumption of good and service, considering that the entire activities are related to the money usage. This research uses PD BPR in Central Java in 2012 (by annual). The analysis technique used is doubled linier regression, whereas the hypothesis test uses t-test to examine the variable influence jointly upon the significance level of 5%. Based upon the research, there is a result that the Capital Adequacy Ratio (CAR) has a positive and not significant effect, the Non-Performing Loan (NPL) has no effect on bank lending. While Interbank Liabilities (ABP) and Third Party Funds (DPK) a significant positive effect on lending PD BPR. To increase lending should perform optimally fund raising, optimizing the usability of financial resources (capital) owned, and have a good credit management that NPLs are in a low level and within the limits required by Bank Indonesia.Keywords: the banking credit distribution, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Interbank Liabilities (ABP), and Third Party Funds (DPK)Â